The Effect of Instructional Approaches and Learning Styles on Students’ Achievement of Grammar - Rista Damesari Saragih; Lince Sihombing; Eddi Setia (Universitas Negeri Medan, 2014)
The objectives of this research are to investigate whether: (1) students’ achievement of grammar taught by applying inductive approach higher than taught by applying deductive approach, (2) achievement of grammar of visual learning style students higher than achievement of grammar of auditory learning style students, and (3) there is an interaction between instructional approaches and learning styles on the students’ achievement of grammar. The population was students of Grade X of Vocational High School 1 Beringin Deli Serdang. Based on Cluster Sampling technique, two classes were chosen, namely Grades X1 and X3. The data were analyzed using a two-way ANOVA with 2 × 2 factorial design. The result reveals that (1) Students` grammar achievement taught by using inductive instructional approach is higher than that taught by using deductive instructional Approach (81,20 > 72,10), (2) Students with visual learning style have higher achievement in grammar than students with auditory learning style (81,90 > 72) and (3) there is significant interaction between instructional approaches and learning styles on students` achievement of grammar (4.906 > 3.96). Thus, it can be concluded that the application of instructional approaches and learning styles can affect students` achievement in grammar. Keywords: Grammar; Instructional Approach; Learning Styles